2015
DOI: 10.1002/bkcs.10063
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effect on trans‐p‐Hydroxybenzylideneimidazolidinone: A DFT Study and Implication to Green Fluorescent Protein

Abstract: In the present study, density function theory (DFT) calculations were carried out regarding the electric field effect on the trans-p-hydroxybenzylideneimidazolidinone (HBDI), which represents the green fluorescent protein (GFP) chromophore. Structures in the absence or presence of electric fields were fully optimized with the CAM-B3LYP functional, and the corresponding absorption properties were obtained by the timedependent DFT method. It was found that electric field parallel to the x-axis (Fx) has the stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Theoretical and experimental studies have examined the influence of electric fields and electrostatics on radiative and nonradiative rates. ,,,, For example, TD-DFT calculations on the isolated GFP chromophore (Figure ) predict that electric fields can change the oscillator strength of an electronic transition and therefore the radiative rate constant. , Park and Rhee performed nonadiabatic molecular dynamics simulations on the GFP chromophore and found that electrostatic effects can outweigh steric factors impeding the twisting of the methine bridge between the phenoxy and imidazolinone rings, suppressing a major pathway for nonradiative relaxation . Drobizhev and co-workers investigated these issues by measuring two-photon absorption cross sections of RFPs .…”
Section: Brightnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental studies have examined the influence of electric fields and electrostatics on radiative and nonradiative rates. ,,,, For example, TD-DFT calculations on the isolated GFP chromophore (Figure ) predict that electric fields can change the oscillator strength of an electronic transition and therefore the radiative rate constant. , Park and Rhee performed nonadiabatic molecular dynamics simulations on the GFP chromophore and found that electrostatic effects can outweigh steric factors impeding the twisting of the methine bridge between the phenoxy and imidazolinone rings, suppressing a major pathway for nonradiative relaxation . Drobizhev and co-workers investigated these issues by measuring two-photon absorption cross sections of RFPs .…”
Section: Brightnessmentioning
confidence: 99%
“…Figure 6. Graphical summary of results from a TD-DFT study performed by Kang et al,97 which demonstrates that the oscillator strength and the absorption maxima for the GFP chromophore can be modulated with changes in the electric field.…”
mentioning
confidence: 99%
“…Deviation from linearity is observed at high values of electric fields, which can be associated with an orbital distortion. 30,31 This, in turn, leads to disturbing the distribution of electron clouds involved in orbitals, which results in a higher overlap during electron transitions. 32 For this reason, in simulations, we have a picture similar to multiphoton absorption, which is observed in laser experiments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%